2010
DOI: 10.1002/pc.21030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ACS modified epoxy resin composites with fly ash and cenospheres as fillers: Mechanical and microstructural properties

Abstract: Composites of diglycidyl ether of bisphenol A resin modified with Amine Containing Silicone as matrix and fly ash and cenospheres as fillers have been examined for their mechanical and microstructural properties. The microstructural features of the composites in terms of free volume size and content, and its influence on the mechanical properties has been investigated. The results indicate that amine containing silicones works as a good coupling agent between the filler and the resin. Composites with 5 phr fly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It is observed that the impact strength increases up to fly ash loading 30%weight and at 40% weight loading there is a decrease in the impact strength because of the high filler content, the polymer availability for filler interaction may be low [9] . Comparatively, surface modified fly ash composites show higher impact strength than the untreated fly ash because of the better dispersion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that the impact strength increases up to fly ash loading 30%weight and at 40% weight loading there is a decrease in the impact strength because of the high filler content, the polymer availability for filler interaction may be low [9] . Comparatively, surface modified fly ash composites show higher impact strength than the untreated fly ash because of the better dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…To provide toughness enhancement, phase separation followed by the slow development of a two-phase morphology is critically important. Therefore, the modification of epoxy should be done to improve its toughening properties and also to get better the dispersion and interfacial bonding of fly ash in epoxy matrix [9] . In this research work modification of fly ash was done using i) surfactant sodium lauryl sulfate and ii) silane coupling agent glycidoxy propyl trimethoxy silane and by iii) size reduction of fly ash was done upto submicron level using high pressure pulverizer.…”
Section: Introductionmentioning
confidence: 99%
“…One major setback of this polymeric resin is its poor resistance to crack initiation and growth. This is thus rendered as brittle along with low impact strength …”
Section: Introductionmentioning
confidence: 99%
“…This is thus rendered as brittle along with low impact strength. 10 The objective of this work was to reduce the brittleness of the epoxy matrix in an eco-friendly way. Here phenalkamine (PA), a new class of curing agent for epoxy was employed.…”
Section: Introductionmentioning
confidence: 99%
“…There are many approaches to improve toughness in epoxy resins [9][10][11][12][13][14][15][16][17][18][19]. One classic route is the addition of nanoparticle fillers, such as layered silicate mineral, SiO 2 , carbon nanotubes, and core-shell nanostructure particles [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%